Opportunities and Challenges in Implementing Green Marketing in The Fish Cracker Home Industry - febri, Rizki Febri Eka Pardani; Siti Rumaanatul Hasanah (Golden Ratio of Social Science and Education, 2025)
This study investigates the implementation potential of green marketing in the fish cracker home industry located in Pesisir Village, Besuki District, using a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis framework. The research reveals that despite operating traditionally and on a small scale, the industry possesses natural strengths aligned with green marketing principles. These include the use of fresh, locally sourced raw materials, low-emission traditional processing methods, and efficient resource use—such as utilizing the entire fish to reduce organic waste. However, key weaknesses were identified, including limited awareness of green marketing concepts, lack of training, constrained access to environmentally friendly technologies, and reliance on plastic packaging. Opportunities for expansion are evident through rising environmental awareness among consumers, especially in urban areas, and consistent demand from neighboring regions like Malang and Madura. Additionally, government support for SMEand sustainable local products offers strategic leverage. Nonetheless, several threats persist, including fluctuating raw material prices, unstructured waste management, and competition from more eco-conscious producers. Supporting and inhibiting factors were analyzed, showing that while internal values and traditional practices support a sustainable approach, limited knowledge and financial capacity hinder full implementation. The study concludes that with targeted interventions such as training, technological assistance, and sustainable packaging innovation, this industry holds significant potential to adopt green marketing as a competitive and responsible strategy. Future research should explore the scalability of these findings across similar rural industries and investigate the long-term impact of green marketing adoption on economic resilience and ecological preservation.